Simuliranje eksplozije pare v reaktorski votlini s splošnim programom za računsko dinamiko tekočin - Leskovar, Matjaž (Strojniški vestnik, 2006)
A reactor cavity steam explosion might occur when, during a hypothetical severe reactor accident, the reactor vessel fails and the molten core pours into the water in the reactor cavity. A steam explosion is a fuel-coolant interaction process where the heat transfer from the melt to the water is so intense and rapid that the timescale for the heat transfer is shorter than the timescale for the pressure relief. This could lead to the formation of shock waves and the production of missiles at later times, during the expansion of the highly pressurized water vapour, which might endanger surrounding structures. The purpose of the paper is to demonstrate how steam explosions can be treated with a general purpose Computational Fluid Dynamics (CFD) code, to give an insight into the steam-explosion phenomenon in a typical Pressurized Water Reactor (PWR) cavity, and to provide a rough assessment of the vulnerabilities of cavity structures to steam explosions. Toachieve this, a fit-for-purpose steam-explosion model was developed, followed by a comprehensive and reasonably conservative parametric steam-explosion study. The multiphase flow in the reactor cavity during the high-pressure pre-mixture expansion was simulated with the CFD code CFX-5.7.1 and the stresses in the reactor cavity walls were determined with the stress-analysis code ABAQUS/Explicit.
Keywords: jedrski reaktorji; nezgode; eksplozije; para; računalniške simulacije